Successful management of a 7-year-old-female with juvenile dermatomyositis at a tertiary hospital in low-income country - Wulandari, Desy; Lubis, Azwin Mengindra Putera; Hikmah, Zahrah; Endaryanto, Anang (Paediatrica Indonesiana, 2024)
Juvenile dermatomyositis (JDM) is a rare chronic autoimmune disease belonging to idiopathic inflammatory myopathies. Pathological skin lesions and proximal weakness primarily characterize this entity, but clinical symptoms can be heterogeneous. Children are more likely to have long-term complications such as lipodystrophy, calcinosis, and vasculopathy. Calcinosis is one of the characteristic sequelae of JDM, despite recent advances in the treatment of JDM, about one-third of patients still develop dystrophic calcinosis. In low-income countries, the availability of medicines is very limited. In our case, a 7-year-old female diagnosed with JDM presented with calcinosis. Aggressive and adequate treatment with steroids, methotrexate, hydroxychloroquine, and aluminium hydroxide can treat the complications. It is challenging to establish an early diagnosis, treatment, prevention of long-term complications, and improved prognosis of JDM, which then will improve the patient’s quality of life, especially in low income countries with limited drug availability.